A construção social da organização: um estudo em duas comunidades rurais - Naves, Flávia Luciana (1997)
This study aims to understand the factors which affect the organization process in two rural communities located in the Lavras, in the south of the Minas Gerais, called Rosas and Cachoeirinha. Through an approach which utilizes, in a complementary form, quantitative and qualitative techniques for data collection, focusing on microstructural aspects without losing sight of the macro context in which the research object is inserted, results which allow on understanding of the importance of elements such as socialization, relationships, culture, communication and influence of outside agents on the behavior adopted by farmers relative to the organization. All these aspects are analyzed from the point of view of farmer, showing the connection among them and their influence upon the organization process, reaffirming the need of deeper analyses when dealing with this subject or promoting some form of intervention in rural communities. Primarily, the way to the organization is through dialogue and agreement between people involved in this process.